Study on horizontal wellbore flow of supercritical carbon dioxide drilling. (5th July 2020) - Xiao, Caiyun; Ni, Hongjian; Wang, Ruihe; Huo, Hongjun; Shi, Xian; Li, Mukun
Highlights: A numerical method of flow field considering CO2 leak-off is developed for CO2 drilling. The flow behavior of SC-CO2 in a horizontal wellbore is analyzed in detail. Annulus pressure and open hole length are major factors affecting CO2 loss factor. CO2 leak-off has little influence on wellbore temperature–pressure distribution. Abstract: The filter loss in the long open hole interval is considerable during horizontal well drilling utilizing SC-CO2, which affects the wellbore temperature and pressure distribution. In this study, a wellbore flow and heat transfer model that considers fluid filtration characteristics, viscous friction heat production and CO2 physical properties is developed. The temperature and pressure are coupled using an alternating direction iterative method and the flow behavior of SC-CO2 in a horizontal wellbore is analyzed in detail. The results indicate that the mass flow rate loss factor can reach 12.33% at a well depth of 5000 m, but the CO2 leak-off has little influence on wellbore temperature–pressure distribution. In addition, phase transition occurs both in the drill pipe and the annulus during CO2 circulation, and wellbore pressure–temperature conditions are highly related to CO2 physical properties. The operating parameters affect the whole wellbore pressure level; however, they have little effect on the temperature of horizontal interval. Furthermore, the annulus pressure level and the open hole length of horizontal interval are major factors affecting CO2 leak-off. The model can help set the optimum drilling parameters during the actual SC-CO2 drilling process to effectively promote the technology.